PEDAGOGICAL TECHNOLOGIES OF CREATIVITY DEVELOPMENT IN FUTURE TEACHERS - Usanov Mehriddin Mustafayevich; Rabbimov Jamoliddin Abdujalalovich (Zeta Repository, 2023)
The article examines the features of the development of creativity in future teachers in the conditions of higher education. The psychological and pedagogical conditions for the formation of creative potential of students are described. The expediency of using heuristic methods in the process of professional training of future teachers is based and their use in the organization of training is analyzed.